Life of Software: A View to Increase Software Life - Ghuge, Avinash; Sharma , Sarika (Gyan Management Journal, 2009)
Software i,s a stl of instruction to acquire inputs and to manipulate them to produce the desired output in terms of functions and performance as determined by the user of the software. It is important to maintain the quality of software. So that life of sofiwtrre will be more increase. Ulhen Life of software will be increase the organizJJ,tion will stable on their business and achieve more benefits like stability of manpower, business operation. They can speedup their business or daily operations. Market is full of competition and it is important to survive into the market. The market need is better quality products. The software is considered as a product and this product is facing lot of problems according to market research. If those factors has been covered or observed carefully the life of the product has been definitely increase. In this paper the current status of the software product has been discussed and the factors are introduced which can increase life of the software.